2020
DOI: 10.1155/2020/4606027
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Music Emotion Classification Method Based on Multifeature Combined Network Classifier

Abstract: Aiming at the shortcomings of single network classification model, this paper applies CNN-LSTM (convolutional neural networks-long short-term memory) combined network in the field of music emotion classification and proposes a multifeature combined network classifier based on CNN-LSTM which combines 2D (two-dimensional) feature input through CNN-LSTM and 1D (single-dimensional) feature input through DNN (deep neural networks) to make up for the deficiencies of original single feature models. The model uses mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
(25 reference statements)
0
31
0
Order By: Relevance
“…Given a sentence with its logical emotion label, LLE extracts affective words from text and attaches the corresponding emotional information to the logical label, which is used to generate the final emotion distribution. Compared to the label enhancement method without using affective words 4 Mathematical Problems in Engineering [23], experimental results demonstrated that the emotion distribution generated by LLE has better performance [24]. In summary, the lack of textual emotional datasets with annotated emotion distributions is a distinct obstacle to the development of EDL.…”
Section: Lexicon-based Label Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…Given a sentence with its logical emotion label, LLE extracts affective words from text and attaches the corresponding emotional information to the logical label, which is used to generate the final emotion distribution. Compared to the label enhancement method without using affective words 4 Mathematical Problems in Engineering [23], experimental results demonstrated that the emotion distribution generated by LLE has better performance [24]. In summary, the lack of textual emotional datasets with annotated emotion distributions is a distinct obstacle to the development of EDL.…”
Section: Lexicon-based Label Enhancementmentioning
confidence: 99%
“…Text emotion classification (recognition) is an important research topic with many promising novel applications [1], such as emotional human-computer interaction [2], intelligent customer service [3], music emotion classification [4], anticipating corporate financial performance [5], and online product review analysis [6]. e goal of text emotion recognition is to find out the writers' emotional states contained in sentences [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shan et al [11] established a recommendation model based on music emotion, mainly studying the emotion conveyed by movie music. Chen and Li [12] used a continuous emotional psychological model and regression model to predict the emotional value of music and used two fuzzy classifiers to measure the emotional intensity to identify the emotional content of music. Rajib Sarkar et al [13] proposed to use convolution neural network to identify music models and compared it with commonly used classifiers such as BP neural network.…”
Section: Introductionmentioning
confidence: 99%
“…But, as the music data are increasing, the error rate of the music classification model based on the neural network to construct a classification of low efficiency is higher and easier to fall into local minimum problem [2]; therefore, the neural network structure should be optimized to establish a music based on particle swarm algorithm to optimize the neural network classification model, speed up the neural network optimization ability, and improve the effect and the music classification accuracy. e music classification model based on particle swarm optimization neural network needs to extract music features, and the extracted music features can describe the music information [3] to effectively identify the music types.…”
Section: Introductionmentioning
confidence: 99%